Urethral plate in tubularized incised plate urethroplasty: how wide is enough? - Zhang, Bin (Transl Androl Urol, 2021)
BACKGROUND: Previous reports found that a preincision urethral plate (UP) width <8 mm increased the occurrence of urethroplasty complications (UCs) in tubularized incised plate (TIP) hypospadias repair. However, is the classification of the UP width based on an 8 mm cut-off value to predict the outcome of TIP urethroplasty objective enough or universally applicable? The purpose of our study was to assess the effect of the UP width on the outcomes of TIP hypospadias repair in the Eastern population we served. METHODS: We retrospectively reviewed the records of patients who underwent TIP hypospadias repair by the same surgeon between August 2013 and December 2019 in our hospital. Data were collected, including demographics, intrinsic parameters of the penis, surgical parameters and subsequent surgical outcomes. The data were analyzed and the cut-off value of the UP width was calculated using a receiving-operator curve. RESULTS: Primary TIP urethroplasty was carried out in 116 patients with a mean age of 35.89±29.40 months. The meatal location was distal in 49 patients, midshaft in 56 patients and proximal in 11 patients. The mean glans width was 12.28±1.36 mm, the mean UP width was 5.74±1.37 mm, the mean neourethral length was 1.96±1.32 cm, and the mean operation duration was 87.52±11.47 min. During a median follow-up of 42 (range: 6 to 80) months, UCs developed in 12 patients, and the UP width was significantly related to the occurrence of UCs (P=0.014). According to the 6 mm cut-off value of the UP width by the receiver operating characteristic curve, patients were divided into two groups. Group A (UP width ≥6 mm) included 69 patients, and Group B (UP width <6 mm), 47 patients. UCs occurred in 3 patients in Group A vs. 9 patients in Group B, P=0.010. CONCLUSIONS: UP width is a potential risk factor for UCs after TIP hypospadias repair. Using this technique with an UP width ≥6 mm is sufficient to result in a good outcome of hypospadias repair.